Los estilos de aprendizaje en la orientación y tutoría de bachillerato - Adán León, Mª Isabel (Revista Complutense de Educación, 2008)
Learning styles in orientation and tutoring in non–compulsory secondary education. The relationship between the learning styless, the kind of non–compulsory secondary education and the academical results are studied in this article, trying to stablish, from the point of view of learning approaches, a psicopedagogical and structural base of an indiviual action in orientation and tutoring. In order to do so, we propose to insert in the curricula activities that mean the beginning of a tutorial thinking frame, at the individual level or even at the group one, that help the pupils to think on their our learning process and to promote flexibility and independence in the way of learning.